2014
DOI: 10.5664/jcsm.3686
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CPAP on Activity Patterns and Diet in Patients with Obstructive Sleep Apnea (OSA)

Abstract: However, there are few studies that have demonstrated the effect of OSA treatment on energy consumption and physical activity. 16,17 Such information is vital, given that both obesity and OSA are independent risk factors for poor health and increased cardiovascular morbidity and mortality. Moreover, lifestyle modifi cations involving diet and physical activity are Study Objectives: Patients with severe OSA consume greater amounts of cholesterol, protein, and fat as well as have greater caloric expenditure. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…Several studies also described relevant secondary outcomes, and therefore had data that were included in other categories. Specifically, the one study included in the energy intake category also contained data on physical activity [47]. One of the studies in the indirect calorimetry category also contained data on energy intake, hormones and physical activity [48].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies also described relevant secondary outcomes, and therefore had data that were included in other categories. Specifically, the one study included in the energy intake category also contained data on physical activity [47]. One of the studies in the indirect calorimetry category also contained data on energy intake, hormones and physical activity [48].…”
Section: Resultsmentioning
confidence: 99%
“…Increased liking for high-fat foods [12] and preference for calorie-rich foods high in fat and carbohydrate [13] were observed in association with OSA severity. Batool-Anwar et al investigated the effects of continuous positive airway pressure (CPAP) on food intake in OSA patients using a Food Frequency Questionnaire (FFQ), and found that CPAP treatment reduced consumption of trans-fat in women, but did not affect overall EI [14]. However, some authors suggest that subjective tools like the FFQ may in fact lead to inaccurate conclusions, including a systematic underestimation of actual EI, and their use should be abandoned [15].…”
Section: Introductionmentioning
confidence: 99%
“…40 Our data may support their data. Thus, preserved dietary habits due to ghrelin-related factors in this study in addition to a decrease in energy expenditure in OSA patients following CPAP treatment might cause body weight gain 41 or make it difficult to lose body weight during CPAP treatment. 21 This study had some limitations.…”
Section: Data Before and After Cpap Treatmentmentioning
confidence: 99%